Peran Komunikasi Antar pribadi dalam Meningkatkan Kondisi Ketahanan Mental Atlet: Studi Kasus Klub Anugerah Gatra ZZ Badminton Academy - Fatin Habibah; Aulian Khairani; Mochammad Mirza (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The focus of this research is the decline in athletes' mental resilience caused by the surrounding environment. The purpose of this study is how interpersonal communication helps athletes improve their mental resilience. The research informants were 11 people, using purposive sampling technique. This research method is descriptive qualitative. According to the results of data analysis, the informants communicate in two directions and verbally and nonverbally during training and matches to conduct directed and organized communication. In this study, the role of interpersonal communication also includes the exchange of expressions that are eager to be said, aiming to solve the problem of non-open communication, which has an impact on the condition of athletes' mental resilience. The challenge faced by athletes is the lack of self-confidence needed to defeat their opponents. Athletes' physical condition is not always stable during training and matches, which leads to mental stress and unpreparedness to face opponents. This is evaluated by considering the experience of failure, feelings, and pressure on oneself.